2014
DOI: 10.1088/0004-637x/788/1/11
|View full text |Cite
|
Sign up to set email alerts
|

BULGE GROWTH AND QUENCHING SINCEz= 2.5 IN CANDELS/3D-HST

Abstract: Exploiting the deep high-resolution imaging of all 5 CANDELS fields, and accurate redshift information provided by 3D-HST, we investigate the relation between structure and stellar populations for a mass-selected sample of 6764 galaxies above 10 10 M ⊙ , spanning the redshift range 0.5 < z < 2.5. For the first time, we fit 2-dimensional models comprising a single Sérsic fit and two-component (i.e., bulge + disk) decompositions not only to the H-band light distributions, but also to the stellar mass maps recons… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

77
388
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 313 publications
(466 citation statements)
references
References 117 publications
(148 reference statements)
77
388
1
Order By: Relevance
“…4 & 5,respectively. sion, than by halo, stellar, bulge or disk mass, bulge-to-total stellar mass ratio (B/T ) or overdensity of galaxies evaluated at the 5th nearest neighbour (δ5). These observational findings are in agreement with prior analyses of the role of central velocity dispersion in quenching (e.g., Wake et al 2012;Teimoorinia, Bluck & Ellison 2016), and are consistent with the strong dependence of central galaxy quenching on surface mass density within 1 kpc (e.g., Cheung et al 2012;Fang et al 2013;Woo et al 2015;Lilly & Carollo 2016) and bulge mass (Bluck et al 2014;Lang et al 2014;Omand et al 2014). Furthermore, we find that varying local density, stellar, halo or bulge mass at fixed central velocity dispersion leads to essentially no impact whatsoever on the quenched fraction (even when these parameters are varied by over three orders of magnitude).…”
Section: What Quenches Central Galaxies?supporting
confidence: 91%
See 3 more Smart Citations
“…4 & 5,respectively. sion, than by halo, stellar, bulge or disk mass, bulge-to-total stellar mass ratio (B/T ) or overdensity of galaxies evaluated at the 5th nearest neighbour (δ5). These observational findings are in agreement with prior analyses of the role of central velocity dispersion in quenching (e.g., Wake et al 2012;Teimoorinia, Bluck & Ellison 2016), and are consistent with the strong dependence of central galaxy quenching on surface mass density within 1 kpc (e.g., Cheung et al 2012;Fang et al 2013;Woo et al 2015;Lilly & Carollo 2016) and bulge mass (Bluck et al 2014;Lang et al 2014;Omand et al 2014). Furthermore, we find that varying local density, stellar, halo or bulge mass at fixed central velocity dispersion leads to essentially no impact whatsoever on the quenched fraction (even when these parameters are varied by over three orders of magnitude).…”
Section: What Quenches Central Galaxies?supporting
confidence: 91%
“…Recent observations have established that the quenched (or red) fraction of central galaxies is most tightly correlated with the inner regions of these galaxies, e.g., surface mass density within 1 kpc, bulge mass or central velocity dispersion (Cheung et al 2012;Wake et al 2012;Fang et al 2013;Bluck et al 2014;Lang et al 2014;Omand et al 2014;Woo et al 2015). Teimoorinia et al (2016) found strong evidence from an ANN analysis that central velocity dispersion is the most predictive, and hence most tightly constraining, observable for central galaxy quenching out of the following list of variables: stellar, halo, bulge and disk mass; local galaxy density and galactic structure (B/T ).…”
Section: Results Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Concurring evidence for the prevalence of high-z disks has come from HST-based studies of rest-UV/optical morphologies and stellar mass distributions of large mass-selected samples out to z ∼ 2.5, which showed that MS SFGs typically have a disk-like stellar structure with a systematic increase of bulge-to-disk ratio towards high masses (e.g. Wuyts et al 2011;Lang et al 2014). These results from kinematics and stellar structure provided some of the compelling evidence that smoother mass accretion modes onto galaxies and internal dynamical processes within galaxies play an important -if not dominant -role in growing galaxies.…”
Section: Kinematics and Structure Of Sfgs And Properties Of Disks Atmentioning
confidence: 99%